2005
DOI: 10.1509/jmkg.69.2.84.60760
|View full text |Cite
|
Sign up to set email alerts
|

Do Satisfied Customers Really Pay More? A Study of the Relationship between Customer Satisfaction and Willingness to Pay

Abstract: Two experimental studies (a lab experiment and a study involving a real usage experience over time) reveal the existence of a strong, positive impact of customer satisfaction on willingness to pay, and they provide support for a nonlinear, functional structure based on disappointment theory (i.e., an inverse S-shaped form). In addition, the second study examines dynamic aspects of the relationship and provides evidence for the stronger impact of cumulative satisfaction rather than of transaction-specific satis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
546
3
24

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 888 publications
(634 citation statements)
references
References 87 publications
14
546
3
24
Order By: Relevance
“…Similarly, Cooil et al, 2007; suggested that the increased income could also be caused to a supplier obtaining an increased portion of satisfied customer's wallet. Homburg et al, (2005) also found that increased cash flows can be attributed through sensitivity of lower price among pleased customers who are willing to pay more. Moreover, the acquisition of additional customers leads to increase revenue.…”
Section: Customer Satisfaction and Financial Performancementioning
confidence: 95%
“…Similarly, Cooil et al, 2007; suggested that the increased income could also be caused to a supplier obtaining an increased portion of satisfied customer's wallet. Homburg et al, (2005) also found that increased cash flows can be attributed through sensitivity of lower price among pleased customers who are willing to pay more. Moreover, the acquisition of additional customers leads to increase revenue.…”
Section: Customer Satisfaction and Financial Performancementioning
confidence: 95%
“…That is, when customers have a higher perceived value in relation to the cost of the product, they are willing to pay a relatively expensive price [72]. In addition, willingness to pay more has a major effect on the enhancement of sales and revenues, so it has been studied in diverse fields [5,73,74]. …”
Section: Willingness To Pay Morementioning
confidence: 99%
“…In today's growing service economy, it is essential for service providers in both the private and public sectors to understand the important roles that creativity, empathy, and implicit knowledge play in service coproduction in order to meet the demand for highly customized, expertise-dependent service experiences (Spohrer et al 2007). These factors are even more linked to the business basis for strong service design when considering the notion that there is a strong relationship between customer satisfaction and "willingness to pay" (Homburg et al 2005).…”
Section: Literature Reviewmentioning
confidence: 99%